2009
DOI: 10.1371/journal.pgen.1000480
|View full text |Cite
|
Sign up to set email alerts
|

synaptojanin1 Is Required for Temporal Fidelity of Synaptic Transmission in Hair Cells

Abstract: To faithfully encode mechanosensory information, auditory/vestibular hair cells utilize graded synaptic vesicle (SV) release at specialized ribbon synapses. The molecular basis of SV release and consequent recycling of membrane in hair cells has not been fully explored. Here, we report that comet, a gene identified in an ENU mutagenesis screen for zebrafish larvae with vestibular defects, encodes the lipid phosphatase Synaptojanin 1 (Synj1). Examination of mutant synj1 hair cells revealed basal blebbing near r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 39 publications
6
91
0
Order By: Relevance
“…Previously, we have shown that in the lateralline organ, synaptic transmission from hair cells is required for postsynaptic spiking (Obholzer et al, 2008). Thus, spiking recorded in response to direct mechanical stimulation of innervated hair cells provides an indirect measure of hair-cell transmission (Trapani et al, 2009). We found that compared with control larvae, a morphant injected with 0.75 mM ribeye b MO showed a slight reduction in the number of spikes recorded in response to a 20 Hz stimulus (Fig.…”
Section: Depletion Of Ribeye Causes Hearing and Balance Defects And Rmentioning
confidence: 58%
“…Previously, we have shown that in the lateralline organ, synaptic transmission from hair cells is required for postsynaptic spiking (Obholzer et al, 2008). Thus, spiking recorded in response to direct mechanical stimulation of innervated hair cells provides an indirect measure of hair-cell transmission (Trapani et al, 2009). We found that compared with control larvae, a morphant injected with 0.75 mM ribeye b MO showed a slight reduction in the number of spikes recorded in response to a 20 Hz stimulus (Fig.…”
Section: Depletion Of Ribeye Causes Hearing and Balance Defects And Rmentioning
confidence: 58%
“…Here it is well established that the unusual arrangement of vesicles in the ribbon and specialized proteins are required for fast docking and efficient exocytosis (40,41). Moreover, specific short-latency calcium channels have been suggested to be involved in allowing rapid vesicle release also in the ongoing response (42) as well as calcium-induced calcium release from specific internal stores (43).…”
Section: Discussionmentioning
confidence: 99%
“…In D. rerio , synaptojanin 1 mutant displays a defect in cone photoreceptor ribbon anchoring, abnormal synaptic transmission at synapses (Holzhausen et al, 2009) as well as a role in maintaining the quantity, fusion and release of synaptic vesicles at hair-cell ribbon synapses (Trapani et al, 2009). In D. melanogaster , synaptojanin is recruited by endophilin to promote synaptic vesicle uncoating (Verstreken et al, 2003).…”
Section: Synaptojaninsmentioning
confidence: 99%